Sex sorting sperm of sumba ongole bulls by using snakehead fish (Channa striata) albumin extract - Maulana, T.; Said, S.; Arifiantini, R. I.; Setiadi, M. A. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The objective of this research was to investigate the potential of snakehead albumin extract (channalbumin) for sorting X and Y sperm of Sumba Ongole (SO) and its characteristic. Semen was collected from three SO bulls using artificial vagina and the freeze dried channalbumin was extracted from snakehead fish. Channalbumin column was made with different concentration ratio of top and bottom fraction: 2%:4%; 3%:5%; 4%:6% respectively and BSA 5%:10% as control. Semen was put in top fraction then incubated for 30 min at room temperature then each fraction was centrifuged at 1800 rpm for 10 minutes. The pellet was evaluated for motility, abnormality, viability, membrane integrity and head sperm morphometric. The results showed that the channalbumin capable to maintain sperm motility in the top fraction better than the bottom fraction. Sperm viability and membrane integrity in control group were significantly higher (P<0.05) than all channalbumin treatment. BSA 5%:10% has highest proportion of X and Y sperm (69%:76.77%) compared with 2%:4% (42.33%:79.13%), 3%:5% (55.97%:75.73%) and 4%:6% of channalbumin (62.77%:68%). It’s concluded that channalbumin 4%: 6% was effective for separation of XY sperm with higher proportion.